Improving Therapy Methods for Citrus Germplasm Exchange - Navarro, Luis; Civerolo, E. L.; Juárez, José; Garnsey, Stephen M. (IOCV, 2022)
Movement of citrus germplasm between citrus-growing countries carries the risk of inadvertent spread of serious virus and viruslike pathogens. Current procedures have not been well tested for all pathogens, or are not completely efficient. The exclusion of the two pathovars of Xanthomonas campestris causing citrus canker and citrus bacterial spot, the greening pathogen, severe isolates of citrus tristeza virus (CTV) and citrus tatterleaf virus (TLV) was studied using a tissue culture quarantine methodology. Infected budsticks were cultured in vitro at 32 C. Shoot tips excised from sprouting buds were grafted in vitro to axenically grown seedlings of Troyer citrange. The citrus canker and the greening pathogens were consistently eliminated, even by grafting large shoot tips of 0.5-0.7 mm. Severe strains of CTV were consistently eliminated only by the use of small shoot tips of 0.15-0.2 mm. TLV was difficult to eliminate, but 42% of the plants propagated from shoot tips with three-leaf primordia were TLV-free. Shoot-tip grafting eliminated greening and CTV from chronically infected plants from Africa and Asia. Severe CTV isolates from Africa, Asia, South America, and North America were also eliminated easily. One isolate of naturally-spreading psorosis from Argentina was also eliminated.